2013
DOI: 10.1177/0971852413498739
|View full text |Cite
|
Sign up to set email alerts
|

Gender Roles in Cotton Production and Management of Related Organizations in Benin

Abstract: Women's productive roles have generated important debates, heuristic as well as practical, in the scientific and development community. In Benin, women farmers are playing a key role, particularly in agriculture and cotton production, where they are involved throughout the production process. However, only a handful of them are involved in the management of farmer organizations. This article aims to identify factors that constrain or enable women's representation in the management of cotton organizations. It u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The result emphasises that female farmers commit more time and effort to their cassava farms than their male counterparts, despite the challenges women encounter with access to resources. This finding agrees with Alidou and Niehof (2013) and Twyman et al (2015), who found that female farmers are more efficient and more productive than their male counterparts, even when their efforts and roles are not publicised.…”
Section: Technology Gap Ratios Meta-technical Efficiency and Determinantssupporting
confidence: 92%
“…The result emphasises that female farmers commit more time and effort to their cassava farms than their male counterparts, despite the challenges women encounter with access to resources. This finding agrees with Alidou and Niehof (2013) and Twyman et al (2015), who found that female farmers are more efficient and more productive than their male counterparts, even when their efforts and roles are not publicised.…”
Section: Technology Gap Ratios Meta-technical Efficiency and Determinantssupporting
confidence: 92%
“…This inequality has lowered women's labor productivity and hence affected contribution of agriculture in improving household livelihood and food security. Alidou and Niehof (2013) reported that women farmers play a great role, particularly in agriculture and cotton production, where they are involved throughout the production process but few of them are involved in the management of farmer organizations. Alidou and Niehof (2013) concludes that gender myths and stereotypes still determine the involvement of women in managing organizations and thus, the male motive in involving women in management continues to remain questionable.…”
Section: Introductionmentioning
confidence: 99%
“…The signi cant in uence of gender on row planting signals possible gender inequalities in access to resources or gender differences in adopting certain agronomic practices (Ndiritu, 2015;Acheampong et al, 2016). The negative association between gender and early planting could indicate the in uence of gender roles or differences in risk-taking and perceptions between men and women farmers (Alidou, 2014;Kangogo et al, 2021;Nigussie et al, 2021). Income status positive association with certi ed seed and crop rotation and negative in uence on pesticide use and early planting could indicate that wealthier farmers may have the nancial capacity to invest in quality and safe inputs as they focus on sustainability or their long-term bene ts.…”
Section: Regression Resultsmentioning
confidence: 99%